2007
DOI: 10.1007/s11540-008-9079-0
|View full text |Cite
|
Sign up to set email alerts
|

The Canon of Potato Science: 35. Seed and Ware Potato Storage

Abstract: What is it?Potatoes will sustain losses during their post-harvest life as they are living organisms with an active metabolism. Depending on storage conditions potato tubers will -to a lesser or greater extent -respire and transpire and thus lose fresh weight. Maintenance and metabolic processes require energy, and potato tubers use part of their dry matter (mainly starch) for necessary energy supply resulting in dry matter loss. Tubers therefore always show a weight loss due to transpiration (water loss) and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 1 publication
0
28
0
Order By: Relevance
“…Dark and lit spaces in the houses, delayed harvest and field pits are among the alternative methods of seed potato storage reported in Eastern Africa [5]. Use of poor storage structures leads to high seed losses and disease spread in storage resulting from poor storage conditions and improper post-harvest handling practices [39,40,41,42]. In addition, poor seed tuber storage leads to deterioration in quality and quality of the seed due to attack by diseases mainly Fusarium dry rot [42].…”
Section: Seed Potato Production Practices By Small-scale Farmersmentioning
confidence: 99%
See 3 more Smart Citations
“…Dark and lit spaces in the houses, delayed harvest and field pits are among the alternative methods of seed potato storage reported in Eastern Africa [5]. Use of poor storage structures leads to high seed losses and disease spread in storage resulting from poor storage conditions and improper post-harvest handling practices [39,40,41,42]. In addition, poor seed tuber storage leads to deterioration in quality and quality of the seed due to attack by diseases mainly Fusarium dry rot [42].…”
Section: Seed Potato Production Practices By Small-scale Farmersmentioning
confidence: 99%
“…Sub-optimal storage environment especially low relative humidity and high temperature leads to increased respiration and transpiration with subsequent loss in food reserves and water respectively. This leads to reduced tuber weight which reduces vigour by depletion of stored food reserves causing poor crop establishment [40].…”
Section: Seed Potato Production Practices By Small-scale Farmersmentioning
confidence: 99%
See 2 more Smart Citations
“…Storage Wustman and Struik (2007) reported that proper storage temperature is 4-5°C for table stock potato. Thus, the VI treatment potatoes in the present study were stored also at 4°C and 90% relative humidity for up to 30 days.…”
Section: Cookingmentioning
confidence: 99%